2021
DOI: 10.18502/jebhpme.v5i3.7292
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Policies for Organizing and Managing Informal Settlements in Iran: A Content Analysis Method

Abstract: Background: Due to the increasing growth of informal and marginal settlements in Iran, the present study was conducted to analyze the contents of upstream national documents regarding city slum in Iran. Methods: This qualitative study with content analysis approach was done in 2020. MAXQDA version 12 software and conventional content analysis method was used to analyze the data. Results: The findings of this study could be classified in two main categories and 11 subcategories. The main categories … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
0
0
Order By: Relevance
“…The findings of this study are consistent with the previous studies that highlighted the importance of usercentered and participatory approaches for developing information systems [24][25][26]. However, various studies also identified some specific challenges and opportunities for content management systems in Iran, such as the lack of standardization, the diversity of user needs, the cultural and linguistic differences, and the legal and ethical issues [27][28][29]. These factors should be considered in the design and implementation of content management systems in Iran and other similar contexts.…”
Section: 3supporting
confidence: 89%
“…The findings of this study are consistent with the previous studies that highlighted the importance of usercentered and participatory approaches for developing information systems [24][25][26]. However, various studies also identified some specific challenges and opportunities for content management systems in Iran, such as the lack of standardization, the diversity of user needs, the cultural and linguistic differences, and the legal and ethical issues [27][28][29]. These factors should be considered in the design and implementation of content management systems in Iran and other similar contexts.…”
Section: 3supporting
confidence: 89%